Application of E-Court in the Trial of Civil Cases of Unlawful Acts (PMH) at the Denpasar District Court - I Gusti Ngurah Agung Suryadinata; Erikson Sihotang; Kadek Dedy Suryana (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
The regulation of electronic evidence in trials is governed by the Electronic Information and Transactions Law. Article 5, paragraph (1) of the Electronic Information and Transactions Law states that electronic information, electronic documents, and/or printouts are valid legal evidence. This means that evidence produced or stored in electronic form is admissible. In its implementation, electronic trials at the Denpasar District Court are regulated by Supreme Court Regulation Number 1 of 2019 and its amendments, as well as Supreme Court Regulation Number 7 of 2022, concerning Electronic Case Administration and Trials in Court. This system allows case registration, payment of court fees, summons, and trials to be carried out electronically through the e-Court application. There are several obstacles in the implementation of electronic evidence at the Denpasar District Court, including a lack of public understanding of electronic evidence, difficulties in ensuring the authenticity and integrity of electronic documents, limited laws and regulations that specifically regulate electronic evidence, and technical obstacles.